El impacto de las Tecnologías de la Información y Comunicación en el desarrollo del sistema cognitivo de los niños de cuarto año de Educación General Básica. - Sánchez Iza, Silvia Marisol (2021)
The present research was develop to solve the following problem: What is the impact of the information and communication technologies to development of the cognitive system of the fourth year of Basic General Education of the School "Mulaló" period 2020 - 2021? For that reason, it is established as general objective to apply strategies of mediation technology in the teaching-learning process to determine the impact on the cognitive system of the students. It has an approach quant using the following methods and techniques. The methodology used is inductive and deductive method, interview, survey, the criteria of specialists, questionnaire, the impact assessment sheet and the analysis of the products of the activity. It was possible to carry out the research and arrive at the following conclusions. As a result, the application was found in the cognitive development of students goes hand in hand with social affective. The physical factors depend to a great extent on the coexistence with the people who are next to the student. For this reason, the involvement of parents were paramount in achieving very high results in the implementation of technology mediation strategies, because they were responsible for providing: internet service, computers, smartphones or tablets, providing the necessary follow-up for the development and success of activities with learners. Additional, the results of the impact of technology mediation strategies on the cognitive system of fourth year students of Basic General Education. According to the technological, mediation strategies are applied to have an impact on students of 89.6%. Therefore, it can be a positive impact when they use strategies of information and communication technologies.